Object location memories recruit distal CA1 and catecholaminergic inputs to proximodistal CA1 - Ana Paula Crestani; Yusuke Teratani-Ota; Brian Joseph Wiltgen (PLoS ONE, 2025)
The hippocampus is thought to combine “what” and “where” information from the cortex so that objects and events can be represented within the spatial context in which they occur. Surprisingly then, these distinct types of information remain partially segregated in the output region of the hippocampus, area CA1. In this region, objects preferentially activate neurons in the distal segment (adjacent to the subiculum) while spatial locations are precisely represented by neurons in the proximal segment (adjacent to CA2). This difference likely results from distinct anatomical connections; proximal CA1 receives direct input from the medial entorhinal cortex (which encodes spatial context) whereas distal CA1 has reciprocal connections with the lateral entorhinal cortex (which encodes objects and events). Based on these findings, it has been proposed that CA1 contains two distinct representations; one that encodes the animal’s spatial location and another that encodes objects that are present in the environment. The current study aimed to determine the role of distal CA1 in learning the location of objects in an environment. To do this, we first demonstrated that distal CA1 is more responsive (higher levels of c-Fos) to objects while proximal is spatially tuned. Further, as previous studies indicate that catecholamines can regulate CA1 activity, we lesioned the catecholaminergic inputs to CA1 and observed a reduction in c-Fos levels in both segments of CA1, and an impairment in object location memory 24h after training. Together, these findings indicate that processing object location in an environment recruits distal CA1 and catecholaminergic inputs to CA1.